New data on harvestmen (Arachnida, Opiliones) of Caucasian glaciers, with descriptions of three new species - Snegovaya, Nataly Y.; Makarova, Olga L. (Zootaxa, 2025)
Three new opilionid species of the family Phalangiidae are diagnosed, illustrated and described from the forelands of two glaciers, Bezengi and Kashkatash, both in the Republic of Kabardino-Balkaria, Central Caucasus, Russia: Rilaena kabardinibalkarica Snegovaya sp. nov., Rilaena kaschkataschica Snegovaya sp. nov., and Opilio bezengii Snegovaya sp. nov. The first description of the female of Metaplatybunus valentinae Snegovaya, 2022 is given.